Meningkatkan Kemampuan Bernalar Kristis Melalui PBL Berbantuan Audio Visual pada Peserta Didik Kelas VIII SMP Santo Yusup Bandung - Christina Desy Priandari; Mawarni Gea; Agustinus Mulyono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research project aims to ascertain the efficacy of the PBL model in enhancing critical reasoning abilities among students at SMP Santo Yusup Bandung. The research is based on the identification of issues pertaining to student engagement, particularly the tendency of students to exhibit minimal attention and participation during classroom discussions. Another issue pertains to cognitive processes, whereby students are prone to being unduly influenced by information that they initially encounter, without engaging in critical reasoning to seek further evidence. Furthermore, learners are inadequately trained in the analysis of information. This research employs a classroom action research design, comprising four phases: planning, implementation, observation, and reflection. The research was conducted in two cycles at Santo Yusup Junior High School in Bandung. The participants were students in class VIIIA, and the material covered was Jesus Proclaimed the Kingdom of God Through Parables and Miracles. The research was conducted in September 2024. The data collection techniques employed included observation, field notes, and the documentation of students' abilities to reason critically. The data analysis employed descriptive qualitative techniques. The findings of the initial cycle of research indicated an enhancement in the capacity to reason critically and a heightened level of student engagement. However, these outcomes did not yet align with the anticipated objectives. In Cycle II, there was a notable enhancement in both critical reasoning and affective learning. The research results demonstrate a 40.12% increase in critical reasoning and learner involvement in Catholic Religious Education. It is hoped that the PBL approach will foster a more active and collaborative learning atmosphere, in alignment with the objectives of the Merdeka Curriculum and the values espoused in the Pancasila Learner Profile. It is anticipated that this research will contribute to the provision of holistic and meaningful education for learners.